2015
DOI: 10.1002/2014jb011760
|View full text |Cite
|
Sign up to set email alerts
|

Structural controls on the emission of magmatic carbon dioxide gas, Long Valley Caldera, USA

Abstract: We present a degassing study of Long Valley Caldera that explores the structural controls upon emissions of magmatic carbon dioxide gas. A total of 223 soil gas samples were collected and analyzed for stable carbon isotopes using a field-portable cavity ring-down spectrometer. This novel technique is flexible, accurate, and provides sampling feedback on a daily basis. Sampling sites included major and minor volcanic centers, regional throughgoing faults, caldera-related structures, zones of elevated seismicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
(120 reference statements)
1
21
0
Order By: Relevance
“…[, ] measured δ 13 C of plume CO 2 degassing from Mount Etna in real time using a Delta Ray tunable diode laser Isotope Ratio Infrared Spectrometer (IRIS) instrument, and Lucic et al . [] sampled soil CO 2 emissions from Long Valley Caldera, U.S., in Tedlar sampling bags and analyzed them for δ 13 C using a Cavity Ring Down Spectrometer. Here we report the first δ 13 C measurements of samples collected at significant distances (up to 5 km) from the source using a helicopter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[, ] measured δ 13 C of plume CO 2 degassing from Mount Etna in real time using a Delta Ray tunable diode laser Isotope Ratio Infrared Spectrometer (IRIS) instrument, and Lucic et al . [] sampled soil CO 2 emissions from Long Valley Caldera, U.S., in Tedlar sampling bags and analyzed them for δ 13 C using a Cavity Ring Down Spectrometer. Here we report the first δ 13 C measurements of samples collected at significant distances (up to 5 km) from the source using a helicopter.…”
Section: Introductionmentioning
confidence: 99%
“…The first measurements of δ 13 C in volcanic plumes were realized by Chiodini et al [2011] at Solfatara, Vulcano, and Etna, who collected plume gases from the crater rims followed by laboratory analyses using gas chromatography coupled with isotope ratio mass spectrometry (IRMS). Since that time Rizzo et al [2014Rizzo et al [ , 2015 measured δ 13 C of plume CO 2 degassing from Mount Etna in real time using a Delta Ray tunable diode laser Isotope Ratio Infrared Spectrometer (IRIS) instrument, and Lucic et al [2015] sampled soil CO 2 emissions from Long Valley Caldera, U.S., in Tedlar sampling bags and analyzed them for δ 13 C using a Cavity Ring Down Spectrometer. Here we report the first δ 13 C measurements of samples collected at significant distances (up to 5 km) from the source using a helicopter.…”
Section: Introductionmentioning
confidence: 99%
“…Applications for instruments using cavity ring-down spectroscopy include monitoring of greenhouse gas emissions (Chen et al, 2010;Crosson, 2008), monitoring carbon storage and sequestration (Krevor et al, 2010), studying plant respiration (Cassar et al, 2011;Munksgaard et al, 2013), and process monitoring in the automotive and pharmaceutical industries (Gupta et al, 2009). Recent attempts to apply this technique to monitoring of active volcanic centers have been successful (Lucic et al, 2014(Lucic et al, , 2015Malowany et al, 2014), but in some instances there have been anomalous responses from the Picarro G1101-i cavity ring-down spectrometers (CRDSs). Volcanoes emit a range of gases whose concentrations can be much higher than their concentrations in the ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Cold temperatures (Hurwitz et al, ) and hydrothermal mineral deposits (Sorey et al, ) in a deep well within the resurgent dome, and an electrically conductive anomaly beneath the dome (Peacock et al, ), suggest instead that this region is a fossil hydrothermal system. The seismic swarms (Hill, ) and shallow geothermal flows (Hurwitz et al, ; Lucic et al, ) occur south of this inferred fossil hydrothermal system.…”
Section: Introductionmentioning
confidence: 91%
“…In contrast, a variety of geological and geochemical measurements suggest that new intrusions are unlikely. There was a great reduction in the intracaldera eruption rate since 650 ka (Hildreth, 2004), there is a modest CO 2 flux on the south flank of the resurgent dome (Bergfeld et al, 2006) that Lucic et al (2015) found is mainly biogenic, heat flow is normal (Hurwitz et al, 2010), seismicity is low (Hill, 2006;Prejean et al, 2002;Shelly et al, 2016), and low Helium isotope ratios do not indicate new magma (Suemmicht et al, 2015). Instead, a number of studies have proposed that the uplift is produced by the upward migration of aqueous fluids released from old, crystallizing magmas at depth (e.g., Hildreth, 2017;Hurwitz et al, 2007;Hutnak et al, 2009).…”
Section: 1029/2017jb014986mentioning
confidence: 99%